2019
DOI: 10.1177/1942775119878464
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Brown on EL Students: Addressing Linguistic and Educational Rights Through School Leadership Practice and Preparation

Abstract: In 1974, the Supreme Court drew on the 1954 Brown decision in Lau v Nichols, placing English learner (EL) students’ right to a meaningful education at the forefront of educational policy. Subsequent federal decisions and legislation (i.e., Castañeda; Equal Educational Opportunities Act [EEOA], No Child Left Behind [NCLB], and Every Student Succeeds Act [ESSA]) have placed the responsibility for providing quality educational programming on districts, schools, and school leaders. In this article, we propose a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Nevada’s restrictive approach is particularly troubling, given both immigrants’ historical presence in the state and its relatively high share of ELs. The state’s antipathy toward immigrants collides with the lack of an EL educational focus in its ESSA plan, which in many ways ignores ELs’ linguistic civil rights (Callahan et al, 2019; DelValle, 2012) via an absence of educational services. We urge educators, researchers, and policymakers in these restrictive, inequitable contexts to carefully consider the long-term costs and consequences of the policies and programs regarding ELs, if not immigrants, in their states.…”
Section: Discussionmentioning
confidence: 99%
“…Nevada’s restrictive approach is particularly troubling, given both immigrants’ historical presence in the state and its relatively high share of ELs. The state’s antipathy toward immigrants collides with the lack of an EL educational focus in its ESSA plan, which in many ways ignores ELs’ linguistic civil rights (Callahan et al, 2019; DelValle, 2012) via an absence of educational services. We urge educators, researchers, and policymakers in these restrictive, inequitable contexts to carefully consider the long-term costs and consequences of the policies and programs regarding ELs, if not immigrants, in their states.…”
Section: Discussionmentioning
confidence: 99%
“…While empirical studies have demonstrated some elements essential to the success of multilingual students in schools, such as relationships with educators, development of academic language, cohesive professional learning, culturally responsive curriculum and pedagogies, additive policies, and systems of support (Araujo, 2009; Bartlett & Garcia, 2011; Miramontes et al, 2011), the literature is lean in offering descriptions of what this looks like in education leadership preparation (Baecher et al, 2013; Callahan et al, 2019; Mavrogordato & White, 2020; Murphy & Torff, 2012; Reeves & Van Tuyle, 2014). Studies that detail examples of the knowledge, skills, and dispositions education leaders need to successfully engage with multilingual learners include: (a) connecting authentically with family and community (Theoharis & O’Toole, 2011), (b) being knowledgeable of sociocultural and sociohistorical foundations of language education (Baecher et al, 2013), (c) collaboratively facilitating program planning and implementation (Baecher et al, 2013), (d) ensuring linguistically responsive instructional materials, curriculum, pedagogical practices and ongoing professional learning through supervision and evaluation processes (Baecher et al, 2016; Murphy & Torff, 2012), and (e) recognizing and working to dismantle systems of linguistic oppression in schools (Theoharis & O’Toole, 2011).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Further, researchers have suggested a principal of the same race often acts as a role model or advocate for their students (Horsford & Tillman, 2012). According to Horsford and Tillman (2012) (Callahan et al, 2019). Linguistic equity permeates decisions about curriculum, assessments, and pedagogy for instructional leaders who strive to serve linguistically diverse learners (Callahan et al, 2019).…”
Section: Leadership Frameworkmentioning
confidence: 99%
“…According to Horsford and Tillman (2012) (Callahan et al, 2019). Linguistic equity permeates decisions about curriculum, assessments, and pedagogy for instructional leaders who strive to serve linguistically diverse learners (Callahan et al, 2019). First, literacy assessment and interpretations of literacy assessment for Black American youth must be done by allowing them to appropriately classify as bilingual, bidialectal, multilingual, or multidialectal speakers given the language of the test (i.e., Standard American English) often tends not to be their first dialect (Smith et al, 2019).…”
Section: Leadership Frameworkmentioning
confidence: 99%
See 1 more Smart Citation